Effect of quark masses on the QCD pressure in a strong magnetic background - Blaizot, Jean-Paul; Souza Fraga, Eduardo; Palhares, Leticia F. (Physics letters, 2013)
We compute the two-loop contribution to the QCD pressure in a strong magnetic background, for arbitrary quark masses. We show that, for very large fields, the chiral limit is trivial.